Modular Synthesis of Trifunctional Peptide-oligonucleotide Conjugates via Native Chemical Ligation - Dastpeyman, Mohadeseh; Karas, John A.; Amin, Azin; Turner, Bradley J.; Shabanpoor, Fazel (Frontiers in Chemistry, 2021)
Cell penetrating peptides (CPPs) are being increasingly used as efficient vectors for intracellular delivery of biologically active agents, such as therapeutic antisense oligonucleotides (ASOs). Unfortunately, ASOs have poor cell membrane permeability. The conjugation of ASOs to CPPs have been shown to significantly improve their cellular permeability and therapeutic efficacy. CPPs are often covalently conjugated to ASOs through a variety of chemical linkages. Most of the reported approaches for ligation of CPPs to ASOs relies on methodologies that forms non-native bond due to incompatibility with in-solution phase conjugation. These approaches have low efficiency and poor yields. Therefore, in this study, we have exploited native chemical ligation (NCL) as an efficient strategy for synthesizing CPP-ASO conjugates. A previously characterized CPP [ApoE(133–150)] was used to conjugate to a peptide nucleic acid (PNA) sequence targeting human survival motor neuron-2 (SMN2) mRNA which has been approved by the FDA for the treatment of spinal muscular atrophy. The synthesis of ApoE(133–150)-PNA conjugate using chemo-selective NCL was highly efficient and the conjugate was obtained in high yield. Toward synthesizing trifunctional CPP-ASO conjugates, we subsequently conjugated different functional moieties including a phosphorodiamidate morpholino oligonucleotide (PMO), an additional functional peptide or a fluorescent dye (Cy5) to the thiol that was generated after NCL. The in vitro analysis of the bifunctional CPP-PNA and trifunctional CPP-(PMO)-PNA, CPP-(peptide)-PNA and CPP-(Cy5)-PNA showed that all conjugates are cell-permeable and biologically active. Here we demonstrated chemo-selective NCL as a highly efficient and superior conjugation strategy to previously published methods for facile solution-phase synthesis of bi-/trifunctional CPP-ASO conjugates.